Desfolha inicial do feijão e seu impacto na habilidade competitiva com plantas daninhas - Cuchi, Marina Luiza (2022)
Among the factors that can cause damage to beans (Phaseolus vulgaris) are the attack of defoliating insects and the interference of weeds in the initial growth stages. Defoliation caused by insects at early crop cycle can alter the bean's competitive ability and result in the anticipation of weed control measures. Therefore, the objective of this work is (1) to evaluate the effect of different levels of defoliation in the early growth stages of common bean and increasing periods of coexistence with weeds on the growth and development of crop; (2) to evaluate the impact of early defoliation of bean in the period prior to weed interference. The research was carried out in the years 202019/2020 and 2020/2021 in an experimental field at the Federal University of Santa Maria-campus Frederico Westphalen. A randomized block design with four replications, in split plots, was used. The factors were tested: seven periods of coexistence with the weeds (0, 7, 14, 21, 28, 35 and all cycle) allocated in the main plots, and different levels of initial defoliation in the common bean (on average 0, 47 and 82 %) allocated in the subplots, after each period the culture was kept free from weed infestation until the end of the cycle. In article I, weed density, leaf area index, soil cover, intercepted photosynthetically active radiation, weed dry mass, total dry mass of beans and plastochron were evaluated. In article II, the number of legumes, weight of legumes, bean yield and determination of the period prior to weed interference were evaluated. It was observed that defoliation significantly reduced the leaf area index and the total dry mass of beans and increased the weed dry mass and plastochron. Defoliation of 78% and 88% under weed coexistence throughout the cycle reduces the total dry mass of beans by up to 79%. Defoliation of 88% increased plastochron at 15°C day node-¹ and 30°C day node-¹ in weedy conditions. High levels of defoliation in the early growth stages of bean reduce the period before interference, occurring at 13 days after emergence for the highest control cost and reduces yield components causing losses of up to 44% in final yield even under weed free conditions and with the weeds. The results indicate the need to integrate the management of insects and weeds in the system in order to avoid yield losses.